Compartment Syndrome following Bothrops Snakebite Leads to Decompressive Fasciotomies - Murilo Sérgio Valente-Aguiar; Bruno Gonçalves da Costa e Silva; Teresa Magalhães; Ricardo Jorge Dinis-Oliveira (Case Reports in Medicine)
Snakebite envenoming is a neglected tropical disease with relevant morbidity and mortality. In this report, we illustrate the clinical course of a suspected Bothrops snakebite envenoming of a patient that evidenced severe pain, edema, pallor, regional lymphadenopathy, ecchymosis, myonecrosis, and bullous erythema in the right lower limb, specially around the fang marks. The clinical course progressed to compartment syndrome followed with decompressive fasciotomies to reduce pressure within the affected compartment.